Hippocampal Functional Dynamics Are Clinically Implicated in Autoimmune Encephalitis With Faciobrachial Dystonic Seizures - Nantes, Julia C.; Thomas, Adam G.; Voets, Natalie L.; Best, Jonathan G.; Rosenthal, Clive R.; Al-Diwani, Adam; Irani, Sarosh R.; Stagg, Charlotte J. (Frontiers in Neurology, 2018)
This is the first study to investigate functional brain activity in patients affected by autoimmune encephalitis with faciobrancial dystonic seizures (FBDS). Multimodal 3T MRI scans, including structural neuroimaging (T1-weighted, diffusion weighted) and functional neuroimaging (scene-encoding task known to activate hippocampal regions), were performed. This case series analysis included eight patients treated for autoimmune encephalitis with FBDS, scanned during the convalescent phase of their condition (median 1.1 years post-onset), and eight healthy volunteers. Compared to controls, 50% of patients showed abnormal hippocampal activity during scene-encoding relative to familiar scene-viewing. Higher peak FBDS frequency was significantly related to lower hippocampal activity during scene-encoding (p = 0.02), though not to markers of hippocampal microstructure (mean diffusivity, p = 0.3) or atrophy (normalized volume, p = 0.4). During scene-encoding, stronger within-medial temporal lobe functional connectivity correlated with poorer Addenbrooke’s Cognitive Examination-Revised memory score (p = 0.03). These finding suggest that in autoimmune encephalitis, frequent seizures may have a long-term impact on hippocampal activity, beyond that of structural damage. These observations also suggest a potential approach to determine on-going MTL performance in this condition to guide long-term management and future clinical trials.